2019
DOI: 10.1080/21691401.2019.1620248
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: GLP-1 receptor agonist lixisenatide protects against high free fatty acids-induced oxidative stress and inflammatory response

Abstract: Increased free fatty acids (FFA) are one of the risk factors for type 2 diabetes. FFA also contribute to endothelial dysfunction in both the prediabetes and diabetes conditions. Therefore, FFA are an important link between diabetes and endothelial dysfunction. In therapeutic application, GLP-1 receptor agonists have been implemented to lower blood glucose in diabetes. Here, we investigate the role of the common clinically used GLP-1 receptor agonist lixisenatide in endothelial cells. We demonstrate that lixise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Generation of ROS was measured by dihydroethidium (DHE) staining (****, P < 0.0001 vs. control group; ### , #### , P < 0.001, 0.0001 vs. OGD/R treatment group, n ¼ 5). Importantly, lixisenatide has shown a protective effect against free fatty acids (FFA)-induced endothelial dysfunction by suppressing the activation of the NF-kB pathway in endothelial cells, 18 which is consistent with the ndings in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Generation of ROS was measured by dihydroethidium (DHE) staining (****, P < 0.0001 vs. control group; ### , #### , P < 0.001, 0.0001 vs. OGD/R treatment group, n ¼ 5). Importantly, lixisenatide has shown a protective effect against free fatty acids (FFA)-induced endothelial dysfunction by suppressing the activation of the NF-kB pathway in endothelial cells, 18 which is consistent with the ndings in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The cells were maintained at 37 C in a 5% CO 2 humidied incubator and used within passage 3-7 at healthy status. For pretreatment, two doses of lixisenatide (10, 20 nM) 17,18 were added to the culture media for 6 hours. For OGD/R conditioning, 95% conuent HUVECs were washed, and the culture medium was replaced with EGM media without glucose.…”
Section: Endothelial Cell Culture Ogd/r and Treatmentmentioning
confidence: 99%
“…Specifically, GLP-1RAs block NLRP3 (Nod-like receptor protein 3h) inflammasome via SIRT1 activation [111]. GLP-1RAs also suppress the nuclear factor-κB (NF-κB) pathway and free fatty acid-induced cellular ROS in endothelium [112]. GLP-1RAs also downregulate the expression of MMPs and tissue inhibitors of MPs (TIMPs) for anti-inflammation [110].…”
Section: Reversing Endothelial Dysfunction By Glp-1rasmentioning
confidence: 99%
“…Liraglutide was found to increase eNOS phosphorylation and nitric oxide (NO) production via AMPK-dependent pathways in endothelial cells ( Li et al., 2016 ; Honda et al., 2018 ; Han et al., 2019 ). Lixisenatide has also been shown to prevent the free fatty acid-induced reduction of eNOS phosphorylation in endothelial cells ( Zhao et al., 2019 ). Sukumaran et al showed that liraglutide improves the renal endothelial dysfunction in obese Zucker rats on a high-salt diet by increasing the renal eNOS expression ( Sukumaran et al., 2019 ).…”
Section: Renoprotective Mechanisms Of Glp-1rasmentioning
confidence: 99%